PELAKSANAAN PUNGUTAN PAJAK BAHAN GALIAN GOLONGAN C DALAM MENUNJANG PENDAPATAN ASLI DAERAH KABUPATEN SOLOK SELATAN - Sri Arnetti; Darnis '; Egy Valia (Fakultas Hukum Universitas Riau, 2014)
Alongwiththeregionalautonomy, lcal government areexpected to be able manage andmaximize eisting resources in theregins for the continuity of theprogress of itself. One of thegovernment 's efforts to increaserevenue kabupaten solok selatanoriginal the area is through thetax excavation category c Ingeneral. the contribution of thetax excavation golongan c thelocal revenue of Kabupaten SolokSelatan, Still relatively small , butsignificant enough in financingadministering government ofKabupaten Solok SelatanKata Kunci : Tax excavacation, pajak